Confocal microscopic imaging of sperm cells: a step toward optimised directional freezing protocols - Iddi, Abdul-Rashid; Sinram, Merve; Leal-Marin, Sara; Winkler, Christina; Will, Fabian; Hubenia, Oleksandra; Tewes, Rouven; Glasmacher, Birgit (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):238